Improving The Ability To Recognize The Concept Of Numbers Through The Utilization Of Dinucard Media (Digital Numeral Card) In Children In Group B2 Ta Hidayatul Mubtadi-in Sawojajar, Kota Malang - Rahmatillah, Ainur Maulidia; Iriyanto, Tomas; Anisa, Nur (Universitas Negeri Malang, 2024)
Number concepts are very important for children to learn basic math concepts that will help avoid failure in the future. This research aims to find out how children aged 5-6 years know the concept of number at Hidayatil Mubtadi-in Sawojajar Kindergarten, Malang City. This research was conducted using the Kemmis and Mc. Taggart followed by 15 children. Data collection techniques include observation, interviews, and documentation used in this study. The results showed that children at Hidayatul Mubtadi-in Sawojajar, Malang City aged 5 to 6 years did not know the concept of number. Keywords: Early Childhood; Number Concept; Media; Digital Numeral Card